If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
3/11 = 6*y // - 6*y
3/11-(6*y) = 0
3/11-6*y = 0
3/11-6*y = 0 // - 3/11
-6*y = -3/11 // : -6
y = -3/11/(-6)
y = 1/22
y = 1/22
| -16=3x+11 | | 20/6•20/7= | | 36=60 | | 69.75/13.95= | | 14s-16.49-1.67=18.4s+10.44 | | -4x+-4+-9=-12x+11 | | -18j-9+8=-7j-1 | | (2m+1)(9)+5(5x+3)= | | 93.65-23.90= | | 0.2(4y-1)-2= | | u/4=17/13 | | 20/3•20/7 | | (-3x^4)(1)= | | -7+6f=5f+7 | | x^2+2y^2+4x+2y-27=0 | | 3(x-7)=5-3x+4 | | -3p=4-2p | | 28x^2-10=14x^2 | | 4p+5-2p+6=3p-4 | | 10+2y=-5y-10+2y | | 10500-6750= | | 3+7y=-4 | | -4+-4+-9=-12x+11 | | 450*15= | | (x+y+1)dx+(-x+y-3)dy=0 | | 4x/30=7x-9 | | X^5+3x^3-1=0 | | -2295+255m=0 | | 9y+1=y-25 | | 78=4p+6 | | 7x=-7+28 | | -9h-(15)=93 |